2001
DOI: 10.1002/chin.200150017
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Single‐Source Sol—Gel Synthesis of Nanocrystalline ZnAl2O4: Structural and Optical Properties.

Abstract: Single-Source Sol-Gel Synthesis of Nanocrystalline ZnAl 2 O 4 : Structural and Optical Properties.-Nanometer-sized particles of the title compound are synthesized from ZnAl 2 (OR) 8 (R: iPr, tBu) by a sol-gel process (iPrOH, 50 • C, 12 h) followed by calcination at 400-1400 • C. As revealed by single crystal XRD the precursor Zn[Al(OtBu) 4 ] 2 crystallizes in the orthorhombic space group P2 1 2 1 2 1 with Z = 4. 27 Al MAS NMR spectroscopy indicates that ZnAl 2 O 4 possesses an inverse spinel structure below 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…7 8 And with the properties of excellent chemical and optical stability, high mechanical resistance, low sintering temperature and high quantum yield, ZnAl 2 O 4 spinel can be used as host material of optical coating, thin film electroluminescence displays, stress imaging device, etc. 9 10 Meanwhile, Nd 3+ -doped inorganic nanomaterials also have been widely studied because of their unique near infrared (NIR) emission, which have significant applications in biological and optical fields. 11 12 For instance, it has been reported that Nd 3+ -doped LaF 3 …”
Section: Introductionmentioning
confidence: 99%
“…7 8 And with the properties of excellent chemical and optical stability, high mechanical resistance, low sintering temperature and high quantum yield, ZnAl 2 O 4 spinel can be used as host material of optical coating, thin film electroluminescence displays, stress imaging device, etc. 9 10 Meanwhile, Nd 3+ -doped inorganic nanomaterials also have been widely studied because of their unique near infrared (NIR) emission, which have significant applications in biological and optical fields. 11 12 For instance, it has been reported that Nd 3+ -doped LaF 3 …”
Section: Introductionmentioning
confidence: 99%